Conference reflections: EUSARF 2012 - Laura Steckley (Scottish Journal of Residential Child Care)
The 12th European Scientific Association on Residential Foster Care for Children and Adolescents Conference (EUSARF) 2012 was held in Glasgow from 3-7th September. Delegates attended from 35 countries spanning five continents, making for a rich international mix. Shortly after, Iain Matheson, a management consultant, researcher, evaluator and educator in New Zealand, started a conversation on LinkedIn, asking for people's reflections on the conference. What follows is an edited version of this discussion, drawing from those participants who gave permission for their contributions to be reproduced here.